EKSTRAK DAUN JERUK PURUT (Citrus hystrix DC) SEBAGAI INSEKTISIDA LARVA NYAMUK Aedes albopictus - Muhamat, Muhamat (Jurnal Riset Industri Hasil Hutan, 2012)
Kaffir lime is one of the plants that produce secondary metabolites. This plant can be used as intercropping plant in the Agroforestry project. Part lime leaves have been used by communities as a refresher, stimulant and insecticide. This study aims to determine the yield of kaffir lime leaves extract and its toxicity against larvae of Aedes albopictus. The extraction method used in this study was maceration with methanol solvent. Yield of extraction Kaffir lime leaves was 8.16%. Toxicity test of Kaffir lime leaves extract against larvae of Aedes albopictus with 24 hours treatment were 2430 ppm for LC50 and 3760 ppm for LC90. This result is classified to the category of low.Keywords : kaffir lime leave, secondary metabolite, intercrooping, ectract, toxicity.